Sprache und Stil im Werk von Alma M. Karlin (University of Maribor Press, 2019)
Language and Style in the Work of Alma M. Karlin. Alma Maksimiliana Karlin (1889–1950) was born in Celje 130 years ago. Since the mid 1920s, she was considered an important world traveler and by the end of World War II Alma Karlin became a very popular and notable German writing author. The volume provides research findings on the linguistic and stylistic aspects as well as some others specific features of Karlin’s literary heritage. The papers are classified according to theoretical, methodological and empirical background and devided into three sections. The contributions in the first part discuss the possibilities of different ap-proaches to studing literary and aesthetic characteristics in Karlin’s select-ed works. Dejan Kos (Maribor) illustrates how Alma M. Karlin’s texts are characterized by an empathetic tendency to transcend the boundaries of her own world through aesthetics and spirituality. The discussion by Sylvia Brä-sel (Erfurt) shows that Karlin does not merely convey knowledge about the world and reflects on entertaining, foreign, and exotic, but also systematically re-presents herself. Alenka Jensterle-Doležal (Prague) describes the ways in which women’s roles and identities are constructed in the novel Svetlikanje v mraku. The analysis of style and language reveals that the author critically asseses woman’s life in a patriarchal society, while advocating racist judgments and prejudices of the time. The article by Melania Larisa Fabčič (Maribor) focuses on Karlin’s autobiography and her style, which is primarily constructed through reflection of emotions, recognized by the reader even when the text does not explicitly demonstrate them. The texts in the second part focus on different approaches of Alma M. Karlin’s textual style. Vida Jesenšek (Maribor) transparently presents the complexity of the author’s style. By implying linguistic, pragmatic and cognitive aspects, the research identifies the connections and mutual correlations between general principles of text’s structure, specific stylistic »meanings« and substantive textual aspects. Inge Pohl (Schwieberdingen) presents the first comprehensive linguistic analysis of the novel Windlichter des Todes, focusing on the archi-tectonic, structure and composition of literary characters and highlightening the function of the narrative perspective and the narrative structure. One of the most outstanding feautres of Alma M. Karlin’s literary texts is conveing emotions. In her research, Hana Bergerová (Ústí nad Labem) demonstrates that Karlin’s describes emotions in different, explicit and implicit, ways. The papers in the third part examine the creative use of language in Alma M. Karlin’s selected works. The reader notices linguistic creativity when rec-ognizing those linguistic meanings or devices in a text which seem unusual, unexpected, or deviating from expected. Urška Valenčič Arh (Ljubljana) studies the use of phraseological expressions in Der blaue Mond’s and compares the original to the Slovene translation. Alja Lipavic Oštir (Maribor) resarches travel texts with a particular emphasis on geographical names. Simona Štavbar (Ma-ribor) proceeds from the assumption that Karlin’s geobiographical texts contain evaluating statements which reinforce social prejudices. It is not surprising, therefore, that there are numerous euphemisms and dysphisms which Karlin uses to »indirectly« denote things, people, and events, concealing or empha-sizing certain judgments. Karlin’s creativity is also reflected in the effective use of word-formations. Inge Pohl (Schwieberdingen) studies neologisms in the novel Windlichter des Todes and describes the word-forming patterns used by Karlin to attract readers’ attention but which also demonstrate her exceptional knowledge of German. The volume offers a scholarly insight into a number of previously unexplored topics related to language and style of Alma M. Karlin’s literary works and outlines possibilities for further researches.